Predicting Unfavorable Treatment Outcomes in Multi-Drug Resistance Tuberculosis Patients: A Retrospective Study in Jakarta, Indonesia - Saila Hadayna; Asri C. Adisasmita; Farida Murtiani (Indonesian Journal of Global Health Research, 2025)
Treatment of multidrug-resistant tuberculosis (MDR-TB) with a short-term regimen offers promise in terms of higher effectiveness and reduced therapy duration. However, treatment failure remains a major challenge in its implementation. This study aimed to identify predictive factors associated with unfavorable treatment outcome (UTO) among MDR-TB patients receiving the short-term regimen in DKI Jakarta Province from 2020 to 2022. Methods: A retrospective cohort study, using data from the National TB Information System (SITB). We retrieved all MDR-TB patients who started short-term treatment regimens at referral hospitals in DKI Jakarta Province in the period January 2020 to December 2022, totaling 166 patients. Each patient was followed for up to 11 months from the initiation of treatment, with final treatment outcomes collected through November 2023. Survival analysis using Cox proportional hazards regression was employed to assess the association between patient characteristics and time to UTO. Results: A total of 43.4% of patients is UTO. The cumulative probability of remaining free from UTO was 38% after day 400. Multivariate regression analysis showed that HIV-positive status (aHR = 2.98; 95% CI: 1.77–4.99) and comorbid diabetes mellitus (aHR = 1.92; 95% CI: 1.19–3.11) were significantly associated with an increased risk of UTO. Conclusion: UTO among MDR-TB patients on the short-term regimen remains high. HIV status and diabetes comorbidity are critical factors influencing treatment outcomes and should be prioritized in clinical management strategies for MDR-TB.